Boosting Oxygen Reduction through Microenvironment Modulation to Enhance Mass Transportation - Bihao Hu; Miao Wang; Danning Li; Jingyi Chen; Chunfeng Li; Lei Wang (Advanced Energy & Sustainability Research, 2023)
Electroreduction of oxygen driven by renewable electricity holds significant promise for the sustainable production of value‐added hydrogen peroxide (H2O2). While water is a desirable source of protons and electrons for this reaction, its low gas solubility often limits the transportation of gas molecules and consequently leads to large concentration overpotential, resulting in unsatisfactory energy efficiencies. Herein, a facile and effective strategy to promote the 2e− oxygen reduction reaction (ORR) through microenvironment modulation is presented. In this work, it is specifically aimed to facilitate oxygen transportation at the reaction interface, particularly at high rates. To achieve this, hydrophobic polytetrafluoroethylene (PTFE) particles are introduced into a catalyst layer containing amino‐group‐functionalized carbon nanotube (CNT‐NH2) as the ORR catalyst for H2O2 production. As a result, the PTFE‐modified CNT‐NH2‐based gas‐diffusion electrode (GDE) substantially improves ORR activity. At 100 mA cm−2, the PTFE‐modified CNT‐NH2 achieves a high cathodic energy efficiency of 92%, 1.5 times higher than the pristine CNT‐NH2‐based GDE (63%). Detailed kinetic analysis reveals that this enhanced ORR performance is indeed due to the enhanced oxygen transportation induced by the persistent hydrophobic microenvironment created by the PTFE‐modified catalyst layer, reducing the concentration overpotential during ORR.